My farm, as it is to be - Chase, E. E. (My University, 1902)
Introduction: My farm is located in Johnson County, Kansas. Kansas City is about 10 miles away. This, with good roads mans about two hour’s drive, or three with a light load. The place is a hilly, clayey sort of land with often found near streams, especially in the eastern part of the state. The soil is fairly deep over most of it. In the south-east corner, however, the rock “crops out”, and we have a quarry of fairly good limestone, and around the quarry, about an acre of shallow land. This at present raises nothing but weeds and bushes. A sort of hill or ridge runs from near the south-west corner of the place in an east-northeast direction, gradually running out a little beyond the center (from east to west) of the farm. A little land on the south side of this ridge (nine acres) is to be put into field crops to keep the horses and cow on. Most of the land, however, is situated on the other side of the ridge, with an east and north-east slope. Along the north side of the place is a dry watercourse or ravine. This is perhaps seventy-five feet lower than the highest part of the farm. In a little delta-like formation at the end of this ravine, near the northeast corner of the place, I shall put a strawberry bed, first digging a ditch and embankment to run the water around. The soil here has been washed down and deposited from the higher parts of the place.
Citation: Chase, E. E. My farm, as it is to be. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Farm; Agriculture; Johnson County Kansas; Kansas City; Theses; Manuscripts (documents)